2012
DOI: 10.1021/bi2017987
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Conserved Interaction Involving the Middle Residue of the SXN Active-Site Motif Is Crucial for Function of Class B Penicillin-Binding Proteins: Mutational and Computational Analysis of PBP 2 from N. gonorrhoeae

Abstract: Insertion of an aspartate residue at position 345a in penicillin-binding protein 2 (PBP 2), which lowers the rate of penicillin acylation by ~6-fold, is commonly observed in penicillin-resistant strains of Neisseria gonorrhoeae. Here, we show that insertions of other amino acids also lower the penicillin acylation rate of PBP 2, but none supported growth of N. gonorrhoeae, indicating loss of essential transpeptidase activity. The Asp345a mutation likely acts by altering the interaction between its adjacent res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 54 publications
1
30
0
Order By: Relevance
“…In the absence of a crystal structure of PBP2 containing the Asp345a insertion, the impact of this mutation is not totally evident, but most likely it is more significant than the C-terminal substitutions. Notably, only an aspartate insertion confers resistance (195), and consistent with this, only an aspartate insertion is observed in clinical gonococcal strains (190). This might suggest that only an insertion of aspartate, not closely related amino acids, such as glutamate or asparagine, can discriminate against ␤-lactam antimicrobials without abolishing the PBP2 transpeptidase activity essential for viability (196).…”
Section: Penicillin Resistancementioning
confidence: 53%
“…In the absence of a crystal structure of PBP2 containing the Asp345a insertion, the impact of this mutation is not totally evident, but most likely it is more significant than the C-terminal substitutions. Notably, only an aspartate insertion confers resistance (195), and consistent with this, only an aspartate insertion is observed in clinical gonococcal strains (190). This might suggest that only an insertion of aspartate, not closely related amino acids, such as glutamate or asparagine, can discriminate against ␤-lactam antimicrobials without abolishing the PBP2 transpeptidase activity essential for viability (196).…”
Section: Penicillin Resistancementioning
confidence: 53%
“…S6, C and D). Although the sequence is not conserved, analogous structures to the L1 loop can be found in class A, B, and C PBPs and perturbation of this loop has been shown to play a role in ␤-lactam resistance (30,38,39). Notably, PBP2x from a highly mutated, penicillin-resistant strain of S. pneumoniae PBP2x, was also found to have variation in positioning of the SXN motif with the serine hydroxyl displaced away from the active site when compared with penicillin-sensitive PBP2x variants (40).…”
Section: Discussionmentioning
confidence: 99%
“…3). Although it has been suggested that this motif plays a role in deacylation in the structurally similar PBP5 of E. coli (30,36,37), perturbation of the SXN motif in PBP2, a transpeptidase from Neisseria gonorrheae, has been previously shown to reduce penicillin acylation rates (39). Future work is needed to determine the individual rate constants of acylation and deacylation in PBP4 and PBP4 CRB to better understand the role of the displaced and/or dynamic motion of the SXN motif in S. aureus PBP4 and the general resistance phenomenon it mediates.…”
Section: Analysis Of S Aureus Pbp4 Structure and Kineticsmentioning
confidence: 99%
“…Note that residues 504 and 510 are in the β3–β4 loop. Flexibility of this loop has been linked to β-lactam resistance in PBP2x from S. pneumoniae [51]. …”
mentioning
confidence: 99%